Developmental Changes in Natural Viewing Behavior: Bottom-Up and Top-Down Differences between Children, Young Adults and Older Adults - Açık, Alper; Sarwary, Adjmal; Schultze-Kraft, Rafael; Onat, Selim; König, Peter (Frontiers in Psychology, 2010)
Despite the growing interest in fixation selection under natural conditions, there is a major gap in the literature concerning its developmental aspects. Early in life, bottom-up processes, such as local image feature – color, luminance contrast etc. - guided viewing, might be more prominent but later overshadowed by more top-down processing. Moreover, with decline in visual functioning in old age, the bottom-up processing is known to suffer. Here we recorded the eye-movements of 7-9 year-old children, 19-27 year-old adults and older adults above 72 years of age while they viewed natural and complex images before performing a patch recognition task. Task performance displayed the classical inverted U-shape, with young adults outperforming the other age groups. Fixation discrimination performance of local feature values dropped with age. Whereas children display the highest feature values at fixated points, suggesting a bottom-up mechanism, older adult viewing behavior is less feature-dependent, reminiscent of a top-down strategy. Importantly, we observed a double dissociation between children and elderly regarding the effects of active viewing on feature-related viewing: Explorativeness correlates with feature-related viewing negatively in young age, and positively in the case of older adults. The results indicate that, with age, bottom-up fixation selection loses strength and/or the role of top-down processes becomes more important. Older adults who increase their feature-related viewing by being more explorative make use of this low-level information and perform better in the task. The present study thus reveals an important developmental change in natural and task-guided viewing.